2020
DOI: 10.1111/nph.16653
|View full text |Cite
|
Sign up to set email alerts
|

A Phytophthora effector protein promotes symplastic cell‐to‐cell trafficking by physical interaction with plasmodesmata‐localised callose synthases

Abstract: Pathogen effectors act as disease promoting factors that target specific host proteins with roles in plant immunity. Here, we investigated the function of the RxLR3 effector of the plantpathogen Phytophthora brassicae.Arabidopsis plants expressing a FLAG-RxLR3 fusion protein were used for co-immunoprecipitation followed by liquid chromatography-tandem mass spectrometry to identify host targets of RxLR3. Fluorescently labelled fusion proteins were used for analysis of subcellular localisation and function of Rx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 80 publications
1
28
0
Order By: Relevance
“…In higher plants, cells are connected through symplastic cell-tocell channels called plasmodesmata (PD) that enable intercellular trafficking of nutrients and signaling molecules. This intercellular transport is regulated by adjusting the size exclusion limit (SEL) of PD that mainly depends upon callose depositions around the PD openings (Tomczynska et al, 2020). Callose deposition upon PAMP perception is crucial for host defense against Phytophthora pathogens (Chang et al, 2015;Du Y. et al, 2015;van den Berg et al, 2018).…”
Section: Modulation Of Cell-to-cell Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…In higher plants, cells are connected through symplastic cell-tocell channels called plasmodesmata (PD) that enable intercellular trafficking of nutrients and signaling molecules. This intercellular transport is regulated by adjusting the size exclusion limit (SEL) of PD that mainly depends upon callose depositions around the PD openings (Tomczynska et al, 2020). Callose deposition upon PAMP perception is crucial for host defense against Phytophthora pathogens (Chang et al, 2015;Du Y. et al, 2015;van den Berg et al, 2018).…”
Section: Modulation Of Cell-to-cell Traffickingmentioning
confidence: 99%
“…PD mediated cell-to-cell movement of P. ramorum hyphae was reported previously (Giesbrecht et al, 2011). A P. brassicae RXLR effector, RxLR3 is shown to inhibit callose deposition at PD by targeting host's callose synthases (CalS) to promote cell-to-cell conductivity that resulted in enhanced infection (Tomczynska et al, 2020). These findings suggest that Phytophthora spp.…”
Section: Modulation Of Cell-to-cell Traffickingmentioning
confidence: 99%
“…The PD-dependent movement of fungal effectors (Khang et al, 2010) and an oomycete effector (Khang et al, 2010; Cao et al, 2018; Tomczynska et al, 2020) have been reported; however, it’s unclear whether bacterial effectors move between plant cells or not. Empirical evidence from this work showed that at least 16 Pst DC3000 effectors move between plant cells through PD.…”
Section: Discussionmentioning
confidence: 99%
“…The oomycete pathogen Phytophthora brassicae RxLR3 effector is localized to PD and physically associated with callose synthases, CalS1, CalS2, and CalS3. The expression of RxLR3 suppresses the function of the CalSs, inhibits the callose accumulation at PD, and promotes the PD-dependent movement of fluorescent molecules (Tomczynska et al, 2020). The bacterial pathogen Pseudomonas syringae pv.…”
Section: Introductionmentioning
confidence: 99%
“…PD allow translocating photosynthetic products from mature leaves (source tissues) to non-photosynthetic parts of the plant (sink tissues; Comtet et al, 2017; Liesche and Patrick, 2017). Recent findings also highlighted the crucial role of PD in plant immunity against filamentous and bacterial pathogens (Lee et al, 2011; Faulkner et al, 2013; Cao et al, 2015; Aung et al, 2020; Tomczynska et al, 2020). The function of PD is controlled by the homeostasis of a plant polysaccharide, callose.…”
Section: Mainmentioning
confidence: 99%